Guideline for Collaboration between Inquiry Officers and Rescuers in Traffic Accident Cases in the Area of Samut Sakhon Province - Ditaem, Raphiya (Suan Dusit Graduate School Academic Journal, 2022)
This research aimed to study roles, duties and operations as well as problems and obstacles in the collaboration between inquiry officers and rescuers in traffic accident cases in the area of Samut Sakhon province. This study was qualitative research that was conducted by interviewing the target groups of 5 inquiry officers and 5 rescuers at Samut Sakhon Charity Foundation obtained by Snowball Sampling. The data were collected by in-depth interviews and the instrument quality was found by an analysis of content validity from experts and the related literature. The results of the research indicated as follows: 1) Currently, the collaboration between the inquiry officers and rescuers focused on preventing the accident especially recording the detail of the accident case such as traffic accident statistics, risk areas, as well as procedures and methods of helping the injured. In each time of helping the injured, a decision was forbidden to be made by sole person. In addition, there must have a doctor, investigator or rescuer who are experienced and skilled at a professional level in the accident scene every time in order to avoid carelessness and mistakes. Inquiry officers were highly crucial to investigating traffic accident cases according to the power of the law. Moreover, inquiry officers should coordinate with relevant officers, such as forensic scientists or scientists, coroners, rescuers. 2) From the study of problems and obstacles in the collaboration between inquiry officers and rescuers in traffic accident case in the area of Samut Sakhon Province, the two main problems were found including the problem of treatment at accident scenes due to the small number of inquiry officers as well as the problem related to the coordination of transportation of the injured, etc.